Congenital myopathies: A clinicopathological study of 25 cases - Jain Deepali; Sharma Mehar; Sarkar Chitra; Gulati Shefali; Kalra Veena; Singh Sumit; Bhatia Rohit (Wolters Kluwer Medknow Publications, 2008)
Objective: Congenital myopathies are rare. Through this article, the authors want to present a clinicopathological analysis of 25 new cases. Materials and methods: The clinical data of patients who were diagnosed with congenital myopathy between 2001 and 2006 was retrieved. Muscle biopsies were processed for H&E staining, enzyme histochemistry, and immunohistochemistry. Biopsies were also processed for ultrastructural analysis. Results: During a period of 6 years, 1.12% of the muscle biopsies were diagnosed as congenital myopathies. The most common congenital myopathy was central core disease followed by nemaline rod myopathy and multi-mini core disease. Clinically, they have variable features. The final diagnosis was made with the help of enzyme histochemistry and ultrastructural features. Conclusion: This study emphasizes the importance of enzyme histochemistry and electron microscopic examination in the diagnosis of congenital myopathies especially in the absence of genetic studies.